The Cambridge companion to Rabindranath Tagore - Chaudhuri, Sukanta, 1950- (Cambridge University Press, 2020)
This is the first one-volume guide in English, or indeed in Bengali, to the full spectrum of Tagore's multi-faceted genius. It has two parts: (a) critical surveys of the chief sectors of his artistic output and its reception; (b) specialized studies of particular topics. The authors are among the leading Tagore experts from India and abroad. They have drawn upon all relevant material in Bengali, English, and other languages, including the entire body of untranslated Bengali works that comprise the greater part of Tagore's oeuvre. They have also considered the historical and cultural context of his time. The book includes an index of all primary works cited, with full details of their complex history of transmission, and a reading list for Tagore studies in English. It will be an indispensable guide for all scholars, students and informed general readers, even those who can access Tagore in Bengali.